The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/s0007114522002434
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate and brain health. Too much ado about nothing or a solution for dementia prevention?

Abstract: Dementia is a significant public health priority with approximately 55 million cases worldwide, and this number is predicted to quadruple by 2050. Adherence to a healthy diet and achieving optimal nutritional status are vital strategies to improve brain health. The importance of this area of research has been consolidated into the new term ‘nutritional psychiatry’. Dietary nitrate, closely associated with the intake of fruits and vegetables, is a compound that is increased in dietary patterns such as the Medit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…However, with emerging evidence, a new perspective has begun to emerge which suggests that increased intake of nitrate may confer certain health benefits (4,8,9) . Indeed, it has now been demonstrated that consumption of dietary nitrate in the form of vegetables/vegetable-derived products can improve markers of cardiovascular (e.g., reduced blood pressure and improved endothelial function) (10)(11)(12)(13)(14) , brain (e.g., improved cognitive function and modulated cerebral blood flow) (15)(16)(17)(18)(19) , and oral (e.g., modified oral microbiome and increased resilience against oral acidification) health (20)(21)(22) . Similarly, nitrate has been shown to improve exercise capacity/performance across a range of population groups (23)(24)(25) , making it a popular ergogenic aid amongst athletes (3,26) .…”
Section: Introductionmentioning
confidence: 99%
“…However, with emerging evidence, a new perspective has begun to emerge which suggests that increased intake of nitrate may confer certain health benefits (4,8,9) . Indeed, it has now been demonstrated that consumption of dietary nitrate in the form of vegetables/vegetable-derived products can improve markers of cardiovascular (e.g., reduced blood pressure and improved endothelial function) (10)(11)(12)(13)(14) , brain (e.g., improved cognitive function and modulated cerebral blood flow) (15)(16)(17)(18)(19) , and oral (e.g., modified oral microbiome and increased resilience against oral acidification) health (20)(21)(22) . Similarly, nitrate has been shown to improve exercise capacity/performance across a range of population groups (23)(24)(25) , making it a popular ergogenic aid amongst athletes (3,26) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, dietary nitrate supplementation has been shown to reduce blood pressure (BP) by between ~2 and 10 mmHg [16][17][18][19][20], and could represent a potential adjunct to traditional antihypertensive medications. In addition, dietary nitrate supplementation has been shown to improve endothelial function [17,21], decrease platelet aggregation [17,19], and, albeit less reliably, enhance cerebral blood flow and cognitive function [22][23][24]. Over 100 studies have also been conducted exploring the potential benefits of dietary nitrate for sports performance, with findings from both a recent meta-analysis [25] and Delphi expert consensus [26] suggesting that nitrate can improve performance across a range of exercise modalities and in various populations.…”
Section: Introductionmentioning
confidence: 99%